Exercise training reduces the frequency of menopausal hot flushes by improving thermoregulatory control. Issue 7 (July 2016) - Bailey, Tom G.; Cable, N. Timothy; Aziz, Nabil; Dobson, Rebecca; Sprung, Victoria S.; Low, David A.; Jones, Helen
Abstract: Objective: Postmenopausal hot flushes occur due to a reduction in estrogen production causing thermoregulatory and vascular dysfunction. Exercise training enhances thermoregulatory control of sweating, skin and brain blood flow. We aimed to determine if improving thermoregulatory control and vascular function with exercise training alleviated hot flushes. Methods: Twenty-one symptomatic women completed a 7-day hot flush questionnaire and underwent brachial artery flow-mediated dilation and a cardiorespiratory fitness test. Sweat rate and skin blood flow temperature thresholds and sensitivities, and middle cerebral artery velocity (MCA v ) were measured during passive heating. Women performed 16 weeks of supervised exercise training or control, and measurements were repeated. Results: There was a greater improvement in cardiorespiratory fitness (4.45 mL/kg/min [95% CI: 1.87, 8.16]; P = 0.04) and reduced hot flush frequency (48 hot flushes/wk [39, 56]; P < 0.001) after exercise compared with control. Exercise reduced basal core temperature (0.14°C [0.01, 0.27]; P = 0.03) and increased basal MCA v (2.8 cm/s [1.0, 5.2]; P = 0.04) compared with control. Sweat rate and skin blood flow thresholds occurred approximately 0.19°C and 0.17°C earlier, alongside improved sweating sensitivity with exercise. MCA v decreased during heating ( P < 0.005), but was maintained 4.5 cm/s (3.6, 5.5; P < 0.005) higher during heating after exercise compared with control (0.6 cm/s [−0.4, 1.4]). Conclusions: Exercise training that improves cardiorespiratory fitness reduces self-reported hot flushes. Improvements are likely mediated through greater thermoregulatory control in response to increases in core temperature and enhanced vascular function in the cutaneous and cerebral circulations.